Research on an Islamic period settlement at Raʾs ʿUshayriq in northern Qatar and some observations on the occurrence of date presses - Petersen, Andrew (Proceedings of the Seminar for Arabian Studies, 2011)
This paper discusses the recent excavations of a late Islamic period site at Raʾs ʿUshayriq in northern Qatar. The site contained a large number of stone buildings including a mosque, a fort, and several houses. The remains include a number of date presses of different types both within houses and within specialized storerooms. The second part of the paper considers the history and development of date presses in the region and the significance of their presence at this site.